Investigating the influence of entrepreneurial behaviour and innovation among undergraduate students of selected universities in Southwest Nigeria - Augustina E. Dada; Omotayo A. Adegbuyi; Mercy Ejovwokeoghene Ogbari (Administrative Sciences, 2023)
Entrepreneurs are those who take initiative and work tirelessly to turn their business ideas into viable, successful companies through innovation. Understanding entrepreneurial behaviour is essential to comprehend how entrepreneurs establish, promote, and expand new businesses. This study investigates the influence of entrepreneurial behaviour and innovation among undergraduate students of selected universities in southwest Nigeria. The target audience was made up of undergraduate students from selected private universities in southwest Nigeria. To be more precise, the purposive sampling method was used to choose the study's participants. To gather information from a varied cross-section of students, 370 copies of the questionnaire were distributed. Only 296 copies of the surveys that were sent out were returned, which indicates an 80.2% response rate. Structural equation modelling was used to examine the data gathered. The results showed that opportunity identification significantly influences innovation more than self-efficacy and risk tolerance. Opportunity identification is the most important factor of entrepreneurial behaviour that helps students to be innovative and become entrepreneurs. The study recommended that to foster entrepreneurship behaviour and innovation among undergraduates, universities in Nigeria should integrate experiential learning opportunities across disciplines to nurture self-efficacy, opportunities identification, and risk tolerance through entrepreneurship education.
Keywords: 350; business ventures; entrepreneurial behaviour; entrepreneurship education; opportunity identification; risk-taking; self-efficacy; innovation